Systemic therapy and perioperative management improve the prognosis of pancreatic ductal adenocarcinoma: A retrospective cohort study of 2000 consecutive cases. (August 2022) - Zhang, Guoxiao; Li, Bo; Yin, Xiaoyi; Gao, Suizhi; Shen, Shuo; Wang, Huan; Shi, Xiaohan; Liu, Wuchao; Zheng, Kailian; Jing, Wei; Zhang, Yijie; He, Tianlin; et al.
Abstract: Objective: This study aimed to explore patterns of the treatment strategies of pancreatic ductal adenocarcinoma based on 2000 consecutive cases of a prospective database since 2012 to obtain new insights for future directions. Methods: Among 2000 patients enrolled in this study, 210 patients were excluded, and 710, 521, and 559 patients were treated between 2012 and 2015 (group 1), between 2016 and 2017 (group 2), and between 2018 and 2019 (group 3), respectively. Patient clinicopathologic and biological factors, and perioperative outcomes were used to assess the prognostic factors. Results: The median survival for all patients with pancreatic ductal adenocarcinoma was 21.7 months (1-year survival, 75.0%; 2-year survival, 43.7%; 5-year survival, 19.7%). Group 3 had a better survival outcome than groups 1 and 2 (median survival time: 23 versus 20.5 and 21.1 months). The proportion of patients younger than 65 gradually increased over time, as did the use of systemic chemotherapy and postoperative adjuvant radiotherapy. The tendency for early diagnosis (lower CA19-9 and CEA levels, smaller size, and earlier N stage), use of chemotherapy and radiotherapy, early recovery (lesser hospital stay and Clavien-Dindo grade <3), absence of abdominal pain, younger age, length of operation ≤3 h, and pathological factors (absence of lymphovascular invasion, peripancreatic fat infiltration and neural invasion, higher differentiation) were related to patients' survival. Multivariable analysis for prognosis revealed that tumor biological factors (increased preoperative serum CA19-9 level, tumor size, tumor differentiation, N stage, and presence of lymphovascular invasion and neural invasion), chemotherapy, radiotherapy, abdomen pain, operation period, length of stay, and length of operation correlated with patients' survival. Conclusions: Systemic therapy, including chemotherapy and radiotherapy, has gradually improved the prognosis after operative resection for pancreatic ductal adenocarcinoma. Neoadjuvant therapy is also beneficial to improve the prognosis to a certain extent. The enhanced recovery after surgery (ERAS) policies and the specific assessment of postoperative pancreatic fistula (POPF) risk may be related to reduced hospital stays and the reduction of serious complications. These advancements show that the concept of systemic therapy has been accepted and actively applied by Chinese medical institutions. Highlights: Systemic therapy and perioperative management have gradually improved the prognosis after operation for pancreatic ductal adenocarcinoma. Neoadjuvant therapy is also beneficial to improve the prognosis to a certain extent. The concept of systemic therapy has been accepted and actively applied by Chinese medical institutions.